2015
DOI: 10.3109/13685538.2015.1025377
|View full text |Cite|
|
Sign up to set email alerts
|

Bladder function in obstructed men – does age matter?

Abstract: Age-related changes in voiding function might not be a result of impaired detrusor contractility or increased outflow obstruction, intrinsic causes must be suspected. Changes in the storage function of the bladder represent specific pathophysiological mechanisms influenced by aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Beltrame supposed that older men with LUTS had significant decreases in voiding efficiency, which might be due to storage dysfunction rather than impaired detrusor contractility or bladder outlet obstruction 8 . Due to lack of report of long term follow-up of the change of detrusor contractility, we tried to investigate a cohort of men and women who had undergone videourodynamic studies (VUDS) before and after more than 10 years to evaluate the changes in detrusor contractility over time.…”
Section: Introductionmentioning
confidence: 99%
“…Beltrame supposed that older men with LUTS had significant decreases in voiding efficiency, which might be due to storage dysfunction rather than impaired detrusor contractility or bladder outlet obstruction 8 . Due to lack of report of long term follow-up of the change of detrusor contractility, we tried to investigate a cohort of men and women who had undergone videourodynamic studies (VUDS) before and after more than 10 years to evaluate the changes in detrusor contractility over time.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of age on contractility is still controversial today. Studies by Beltrame et al in 2015 in humans and Hardy et al in 2019 in mice did not show a relationship between age and contractility, 16 , 17 whereas a 2010 review of the literature concluded that contractility progressively decreased with age. 18 Prostatic volume was also not correlated with contractility.…”
Section: Discussionmentioning
confidence: 95%
“…There was an independent age-associated decline in contractility. Literature on the association of age and bladder contractility is conflicting [11], but others studies have reported a similar association with age [7,8,12]. Age can impact bladder contractility by several possible mechanisms.…”
Section: Figurementioning
confidence: 99%